2010
DOI: 10.1111/j.1467-7717.2009.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Flood proneness and coping strategies: the experiences of two villages in Bangladesh

Abstract: This paper explores peoples' indigenous survival strategies and assesses variations in people's ability to cope with floods in two flood-prone villages in Bangladesh. It reveals that people continuously battle against flood vulnerability in accordance with their level of exposure and abilities, with varied strategies employed at different geophysical locations. The paper reports that people in an area with low flooding and with better socioeconomic circumstances are more likely to cope with impacts compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 34 publications
6
99
0
Order By: Relevance
“…This supports our theoretical argument that individuals prefer to stay and try to adapt to an environmental problem -instead of opting for the more uncertain and costly option of migration when facing long-term environmental shocks. Our study compliments the findings of previous studies, which report that short-term environmental events can lead to migration (e.g., Gray and Mueller 2012a;Paul and Routray 2010), while we additionally provide new evidence on the nexus between long-term environmental events and migration in the context of micro-level studies.…”
Section: Resultssupporting
confidence: 77%
“…This supports our theoretical argument that individuals prefer to stay and try to adapt to an environmental problem -instead of opting for the more uncertain and costly option of migration when facing long-term environmental shocks. Our study compliments the findings of previous studies, which report that short-term environmental events can lead to migration (e.g., Gray and Mueller 2012a;Paul and Routray 2010), while we additionally provide new evidence on the nexus between long-term environmental events and migration in the context of micro-level studies.…”
Section: Resultssupporting
confidence: 77%
“…For example, a study by Concern Universal Bangladesh (2010) found that although the most vulnerable households were aware of the measures that should be taken to reduce the risks to their households, they were unable to implement those measures due to lack of resources. Further, Paul and Routray (2010) emphasised the ineffectiveness of individual, often indigenous, coping strategies beyond a critical threshold, requiring people to seek the safety of places like cyclone shelters when the flood level increases.…”
Section: Disaster Risk Reduction Infrastructurementioning
confidence: 99%
“…The monga stricken people, in the northern region, represents 10 percent of the country's total population and occupies 11 percent land of Bangladesh (Rob, 2005). This periodic catastrophe has long been linked with the country's traditional subsistence agriculture system, feudal and tenure arrangement and exploitative dadan 2 system in rural credit market (Elahi & Ara, 2008;Paul & Routray, 2010a). Similarly, transport crisis, inadequate marketing, limited irrigation facilities and employment crisis in the monga prone region increase people's vulnerability to a great extent (Zug, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Floodplain topography and tropical monsoon climate make northern region of Bangladesh vulnerable to various natural calamities such as flood, riverbank erosion, drought and cold waves, all of which occurs more frequently and intensely than other regions of the country (Paul & Routray, 2010a;Paul et al, 2012;Paul, 2014). Amidst these compelling conditions, the local economy shows little diversification and is heavily dependent on agriculture, which yields only one or sometimes two annual harvest, in contrast with three crops per year in more fertile and benign parts of the country (Ara, 2007;Paul & Routray, 2010b).…”
Section: Introductionmentioning
confidence: 99%